Clinical and imaging features of male breast disease, with pathological correlation: A pictorial essay. Issue 2 (16th May 2013) - Ng, Angeline Mei Lian; Dissanayake, Deepthi; Metcalf, Cecily; Wylie, Elizabeth
Summary The majority of male breast diseases are benign. The most common is gynaecomastia. Although it is rare, the most critical diagnosis is a malignancy. Radiologists are generally less familiar with breast disease in males compared with females. This pictorial review will highlight the ultrasonographic, mammographic and pathological features of a spectrum of benign and malignant male breast diseases. This includes gynaecomastia, fat necrosis, lipoma, epidermoid cyst, subareolar abscess, chronic inflammation, melanoma and ductal carcinoma.